Long-term Outcomes of Living Kidney Donation. Issue 6 (June 2016) - Slinin, Yelena; Brasure, Michelle; Eidman, Keith; Bydash, Jason; Maripuri, Saugar; Carlyle, Maureen; Ishani, Areef; Wilt, Timothy J.
Abstract : Background: In an effort to improve outcomes associated with living kidney donation, the Kidney Diseases Improving Global Outcomes (KDIGO) assembled a Work Group to develop comprehensive guidelines addressing the evaluation and care of living kidney donors. We conducted this systematic review to inform guideline development. Methods: We searched Ovid Medline, Ovid Embase, and the Cochrane Library to identify systematic reviews, randomized controlled trials, and observational studies published through September of 2014 and consulted the KDIGO Expert Work Group. We extracted data from systematic reviews and observational studies with sample size over 100 and mean follow-up time of at least 5 years. Studies had to have an adequate comparison group that excludes subjects with contraindications to kidney donation. Results: For the long-term donor outcomes, we extracted 5 systematic reviews and 40 observational studies. Moderate grade evidence reveals an association between living kidney donation and greater risk of end-stage renal disease. This association is true for donors of all races with African American donors sustaining the greatest increase in absolute risk. We found very low grade evidence that kidney donation is associated with lower kidney function, proteinuria, hypertension, and psychosocial outcomes. Consistent evidence from 3 studies reveals that donors are at higher risk for preeclampsia and gestational hypertension with postdonation pregnancies and compared with healthy matched nondonors. Conclusions: Living kidney donation appears to be associated with a small absolute increase in risk of end-stage renal disease, hypertension, and pregnancy complications, such as preeclampsia and gestational hypertension. Abstract : Supplemental digital content is available in the text.